أثر المتغيرات الاقتصادية الكلية على معدل البطالة دراسة قياسية لحالة الجزائر خلال الفترة 1990-2018 - زليخة, مرداسي; دلال, غريسي علوي; حياة, وصيف محمد بن بورقعة (University of eloued جامعة الوادي, 2020)
"الملخص تعتبر البطالة إحدى المشكلات الأساسية التي تواجه معظم دول العالم باختلاف مستويات تقدمها ،هذه المشكلة كانت محل بحثنا حيث تم قياس أثر المتغيرات الاقتصادية الكلية على معدل البطالة في الجزائر خلال الفترة 1990-2018،وذلك بعد معالجته من جانبين: جانب خاص بالإطار النظري الأدبيات النظرية للبطالة والمتغيرات المؤثرة فيها والدراسات السابقة، ومن ثم الدراسة القياسية في الجانب التطبيقي ببناء نموذج قياسي لقياس أثر المتغيرات الاقتصادية الكلية على معدل البطالة في الاقتصاد الجزائري. ومن خلال هذه الدراسة قمنا ببناء نموذج قياسي متعدد وARDL،فتبين أنه توجد علاقة بين التضخم والنمو الاقتصادي وأسعار البترول علاقة طردية أما بالنسبة للإنفاق الحكومي علاقة عكسية مع البطالة . ""The unemployment is one of the basic prblems facing most countries of the world with different levels of progress;this problem was the subject of our research;as the effect of macroecoeconomic variables on the unemployment rate in algeria during the period 1990_2018 was measured;this is aftter dealing with two aspects :a part related to the theoretical framework;the theoretical literature on unemployment ;the variables affecting it;and previous studies,and then the standard stady on the practical side by building a standard model to measure the efect of macroeconomic variables on the unemployment rate in the algerian economy .and through this study;we built a multi_standard model and ARDL .it was faoud that there is a relationship between inflation ,economic growth and oil prices ,a positive relationship .as for government spending ,an inverse relationhip with unemployment . key words:unemployment,the algerian economy,ARDL model "
مذكرة ماستر اقتصاد كمي
Keywords: ،البطالة، الاقتصاد الجزائري ، نموذج ARDL.; unemployment,the algerian economy,ARDL model